Multi-electron transfer enabled by topotactic reaction in magnetite - Wei Zhang; Yan Li; Lijun Wu; Yandong Duan; Kim Kisslinger; Chunlin Chen; David C. Bock; Feng Pan; Yimei Zhu; Amy C. Marschilok; Esther S. Takeuchi; Kenneth J. Takeuchi; et al. (Nature Communications, 2019)
In contrast to the conventional wisdom on conversion-driven structural collapse of the host, this work shows that lithium conversion in magnetite resembles the intercalation process, going via topotactic reactions, thereby enabling multi-electron transfer and high reversible capacity.